Determinants of Recent HIV Self-Testing Uptake Among Men Who Have Sex With Men in Jiangsu Province, China: An Online Cross-Sectional Survey - Jianjun Li; Gifty Marley; Gifty Marley; Ye Zhang; Yunting Chen; Weiming Tang; Weiming Tang; Yu Rongbin; Gengfeng Fu (Frontiers Media S.A., 2021)
Background: To help inform regarding HIV self-testing (HIVST) upscale, we assessed the determinants of recent HIVST uptake among men who have sex with men (MSM) in Jiangsu province, China.Methods: We conducted a convenience online survey from March to April, 2020 among men aged ≥16 years, who had ever had sex with other men. Statistical analysis included Pearson's chi-square test, bivariate correlation, and multivariable logistic regression. p < 0.05 was considered statistically significant.Results: Of the total 692 participants, 69.5% (481) were aged between 18 and 40 years, and 65.9% (456) had reportedly ever self-tested. Using HIVST for first HIV test (aOR = 1.98, 95% CI: 1.21-3.26), perceiving HIVST as more private (aOR = 1.41, 95% CI: 0.85-2.35), and users not needing to go to a health facility (aOR = 1.68, 95% CI: 1.20-2.34) were associated with recent HIVST as facilitating factors.Conclusion: HIVST uptake rate has increased among Jiangsu MSM and can be further promoted by healthcare workers routinely recommending HIVST to their clients.